Optimization of essential oil extraction from zingiber officinale - Noor Amiza, Amiril (2006)
The production of essential oils from natural sources is a highly profitable nowadays. The herbaceous perennial of cooking ginger has been used in culinary uses and home remedies since ancient time. Cooking ginger is also known scientifically as Zingiber Officinale spp. The extraction process of ginger is conducted by undergoes the sample of rhizome which part of the plant contains the active compound of essential oil and pungent compound using hydrodistillation method. The components of the essential oil will be decomposed and will create new components that is unidentified if the extraction process undergoes in high temperature. Hence this study is focused to optimize the condition of hydrodistillation which are the size of sample and time of experiment conducted to extract the essential oil from ginger to yield better essential oil without decompose its components. Then the essential oil obtained will be diluted in n-hexane before analyzed it by Gas Chromatography using the Flame Ionization Detector, (GC-FID). The result obtained from the analysis will be compared between the data gained from the analysis of the reference compound of cineol and compare the result between the data obtained with the reference data of cineol and hydrocarbon. Qualitative analysis shows the powder size yields more essential oil than slices size while quantitative analysis shows the samples of Eoil1 and Eoil2 did yield the marker compound of 1, 8-cineol.